2016
DOI: 10.1001/jamainternmed.2015.7479
|View full text |Cite
|
Sign up to set email alerts
|

Examining Variation in Hospice Visits by Professional Staff in the Last 2 Days of Life

Abstract: IMPORTANCE In the final days of life, symptoms are exacerbated and often families need both education and emotional support from hospice professional staff. The Medicare Hospice Benefit provides a per-diem payment with no requirements on the frequency of patient visits. OBJECTIVE To examine individual characteristics, hospice program, and geographic variation in hospice visits by professional staff during the last 2 days of life. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study of 661 557 Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Decedent race/ethnicity was not tested because of sensitivities around such adjustment. With respect to setting of care, prior studies have suggested substantially different care processes and reports of care experiences by setting 5,21 and have demonstrated associations between both hospice profit status and setting as well as profit status and care processes. 22 True differences in quality of care across c Note that, as is often the case, bivariate and multivariate regression coefficients differ in sign in several instances, so that unadjusted RRs may be higher for a group (e.g., caregivers of male decedents) associated with a lower adjusted (multivariate) odds ratio of responding.…”
Section: Discussionmentioning
confidence: 99%
“…Decedent race/ethnicity was not tested because of sensitivities around such adjustment. With respect to setting of care, prior studies have suggested substantially different care processes and reports of care experiences by setting 5,21 and have demonstrated associations between both hospice profit status and setting as well as profit status and care processes. 22 True differences in quality of care across c Note that, as is often the case, bivariate and multivariate regression coefficients differ in sign in several instances, so that unadjusted RRs may be higher for a group (e.g., caregivers of male decedents) associated with a lower adjusted (multivariate) odds ratio of responding.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately not all caregivers and patients receive a visit on the day of patient death, despite the fact that the hospice Medicare benefit does not restrict visit number and that patient symptoms are often exacerbated as death approaches (Teno, Plotzke, Christian, & Gozalo, 2016). This study reported on patients who did not receive a hospice visit within 48 hours of death, finding concerning disparities using an analysis of hospice administrative data (Teno et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This study reported on patients who did not receive a hospice visit within 48 hours of death, finding concerning disparities using an analysis of hospice administrative data (Teno et al, 2016). Patients who were black were 30% less likely to get visits, one in five persons dying in a nursing home did not get a hospice visit, and one in five dying on a Sunday did not get a visit (Teno et al, 2016). This precludes supporting caregivers and patients during a particularly vulnerable time.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Hospice visits in the last days of life vary substantially by race, hospice program, and geographic region of the country. 46 …”
Section: Aca Impact On End-of-life Carementioning
confidence: 99%